Radio view of a broad-line Type Ic supernova ASASSN-16fp. Issue 1 (13th March 2020) - A. J., Nayana; Chandra, Poonam
ABSTRACT: We present extensive radio observations of a Type Ic supernova, ASASSN-16fp. Our data represent the lowest frequency observations of the supernova beyond 1000 d with a frequency range of 0.33–25 GHz and a temporal range of ∼8–1136 d post-explosion. The observations are best represented by a model of synchrotron emission from a shocked circumstellar shell initially suppressed by synchrotron self-absorption. Assuming equipartition of energy between relativistic particles and magnetic fields, we estimate the velocity and radius of the blast wave to be $v$ ∼ 0.15 c and r ∼ 3.4 × 10 15 cm, respectively, at t 0 ∼ 8 d post-explosion. We infer the total internal energy of the radio-emitting material evolves as E ∼ 0.37 × 10 47 ( t / t 0 ) 0.65 erg. We determine the mass-loss rate of the progenitor star to be $\dot{M} \sim (0.4\!-\!3.2) × 10^{-5}\, M_{\odot }\, \rm yr^{-1}$ at various epochs post-explosion, consistent with the mass-loss rate of Galactic Wolf–Rayet stars. The radio light curves and spectra show a signature of density enhancement in the circumstellar medium at a radius of ∼1.10 × 10 16 cm from the explosion centre.